Kajian Pemanfaatan Purun Dan Serbuk Gergajian Limbah Industri Kerajinan Masyarakat (Ikm) Sebagai Papan Partikel: Study On The Utilization Of Purun And Sawsdowns From Small Medium Industry (SMI) Waste As Particle Board - Supriyati, Wahyu; Usop, Linggua Sanjaya; Adiwijaya, Saputra; Budayanti, Tari; Wulandari, Agtri; Alpian, Alpian (JURNAL HUTAN TROPIKA, 2025)
Purun waste and sawdust are generally thrown away, not used by the community. This study examines the utilization of purun waste and sawdust with polyurethane adhesive. Purun is mixed with ironwood sawdust in a ratio of 5% and 95%; 10% and 90%; 0% and 100%. The adhesive used is 10% of the material weight. The particleboard is hydraulically pressed at a temperature of 105oC with a pressure of 15 kg/cm2 for 15 minutes. Each treatment is repeated 3 times. The results show that particleboard made from purun waste and sawdust has physical properties (water content and density) and mechanics that meet the requirements of SNI. 03-2105-2006, except for the MoR value. The addition of purun in the composition of particleboard materials does not significantly affect the properties of particleboard so it can be used as an alternative raw material.